Adsorption of Textile Dye by Activated Carbon Made from Rice Straw and Oil Palm Midrib - Mochamad Lutfi Firdaus; Noli Krisnanto; Wiwit Alwi; Ronald Muhammad; Muhamad Allan Serunting (Graduate Program of Syiah Kuala University, 2017)
Synthetic dye wastewater from textile industries is characterized by strong color, high temperature, variable pH and high chemical oxygen demand (COD). The strong color of wastewater affects aesthetic and water transparency of water bodies. The metabolites could be toxic to aquatic biota and posing a potential hazard to human health. Eventually, it will cause severe environmental problems. One of method that has advantages in term of simplicity to remove synthetic dyes is adsorption. Environmentally benign and low-cost materials to make adsorbent are biomass-based materials. Two different biomaterial wastes of rice straw and oil palm midrib were used in this study to develop activated carbon adsorbents. These adsorbents were applied for the removal of Naphtol AS-G dye in aqueous solution. The effects of solution pH, adsorbents masses and contact time on dye adsorption were evaluated based on batch experiments. Removal of dye can be achieved within 60 minutes at a wide pH range starting from 4 to 8. At lower pH, synthetic dye removal was decreasing probably due to protonation of adsorbent’s active sites. The adsorption isotherms based on Langmuir and Freundlich models were analyzed. The isotherms analysis indicated that the adsorption by rice straw and oil palm can be represented by Langmuir and Freundlich isotherm model, respectively. Adsorption isotherms of Naphtol AS-G onto activated carbon are favorable with high adsorption capacity for both biomaterials. The mechanisms of color removal by activated carbon involved chemical and physical adsorption, in accordance with both the Langmuir and Freundlich models. The calculated maximum dye adsorption capacities onto rice straw and oil palm midrib activated carbon were 55.86 and 69.44 mg/g, respectively. Adsorption using biomass-based activated carbon offers a good technique for textile wastewater treatment as it could remove up to 95% of the color intensity besides reducing other pollutants such as COD, nitrate and phosphate.